The Effect of High Voltage Electrical Discharge on the Physicochemical Properties and the Microbiological Safety of Rose Hip Nectars - Nela Nedić Tiban; Mirela Šimović; Martina Polović; Antonija Šarić; Ivana Tomac; Petra Matić; Lidija Jakobek (Foods, 2022)
Although neglected as an industrial raw material, rose hip has been important for both nutritional and medical purposes for centuries. The main goal of this study was to propose a rapid and inexpensive non-thermal technique such as high voltage electrical discharge (HVED) to preserve valuable rose hip bioactive compounds, towards the development of high-quality products, including low-calorie products. The objective of this work was to evaluate the effects of HVED on the physicochemical properties and the microbiological safety of rose hip nectar formulations and, for comparison, on a pasteurised sample. Physicochemical analysis proved that rose hip pulp and the prepared nectars were valuable sources of polyphenols and ascorbic acid with high antioxidant activity. The HVED technique had minimal effects on the quality characteristics of the nectars under the different process conditions (50, 100 Hz; 10, 15, 20 min). In addition, the pasteurised nectar showed the greatest loss of ascorbic acid (54%) and phenolic compounds (40%). The microbiological quality of nectars was examined immediately after preparation/treatment and after 6 and 12 days of storage at 4 °C. In addition to the pasteurised sample, HVED-treated rose hip nectar prepared from microwave-blanched puree with extended shelf life had satisfactory microbiological safety after storage.